Modern Art In Animation: Bringing Van Gogh’s ‘The Starry Night’ Alive - Aliah Hana Ruzaidi (Journal of Computing Technologies and Creative Content, 2022)
The Starry Night, painted by Vincent Van Gogh in an asylum in Saint-Rémy, is one of the most famous paintings of human history. Van Gogh is commonly dubbed as the ‘tortured artist’ who cuts off his own ear due to a declining mental state. When a Chinese company named Motion Magic decides to turn three of his masterpieces (The Starry Night, The Yellow House and Bedroom in Arles) into one 2-minutes long 3-Dimensional Virtual Reality animation, they did not just give birth to a mere video – they provide an experience for the viewers to live inside the eccentric world of Van Gogh, and indulging in his life from inside out. The viewers could feel the last bits of loneliness that Van Gogh suffers from when he decided to end his life – the artist with only one out of 860 oil paintings in his life sold. The art from the 1800s combined with the advancement of technology in the 2010s is surely something impressive to behold, something that could not be imagined in the olden times.